2017
DOI: 10.1038/s41598-017-11741-9
|View full text |Cite
|
Sign up to set email alerts
|

An Affordable Wet Chemical Route to Grow Conducting Hybrid Graphite-Diamond Nanowires: Demonstration by A Single Nanowire Device

Abstract: We report an affordable wet chemical route for the reproducible hybrid graphite-diamond nanowires (G-DNWs) growth from cysteamine functionalized diamond nanoparticles (ND-Cys) via pH induced self-assembly, which has been visualized through SEM and TEM images. Interestingly, the mechanistic aspects behind that self-assembly directed G-DNWs formation was discussed in details. Notably, above self-assembly was validated by AFM and TEM data. Further interrogations by XRD and Raman data were revealed the possible gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Similarly, Guo et al described that the thermal conductivity of DNWs may rise with respect to the increase in length and cross-sectional areas [74]. Recently, as seen in Figure 7, our group also proved the downfall in the conductivity of a single G-DNW with respect to a decrease in temperature [63]. Overall, it has been concluded that between 0 and 1000 K, DNW's thermal conductivities firstly upsurge with an increasing temperature and then dropdown.…”
Section: Thermal Conductivity and Electrochemical Properties Of Dnwssupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, Guo et al described that the thermal conductivity of DNWs may rise with respect to the increase in length and cross-sectional areas [74]. Recently, as seen in Figure 7, our group also proved the downfall in the conductivity of a single G-DNW with respect to a decrease in temperature [63]. Overall, it has been concluded that between 0 and 1000 K, DNW's thermal conductivities firstly upsurge with an increasing temperature and then dropdown.…”
Section: Thermal Conductivity and Electrochemical Properties Of Dnwssupporting
confidence: 75%
“…But it is also essential to make them with reproducibility and uniformity. To this footpath, recently, our group report the pH-induced electrostatic self-assembly of novel cysteamine functionalized diamond nanoparticles (ND-Cys) to evidence hybrid G-DNW growth [63]. Those G-DNWs are highly stable in respective pH buffers, but if more amount of DI-water is added, the longer nanowires (initially at ~100 μm) break into small wires/rods (few microns).…”
Section: Wet Chemical Route To Synthesis Dnwsmentioning
confidence: 99%
“…As reported earlier, self-assembled diamond nanoparticles (DNPs) tend to form graphite sheath over NW-like structure via electrostatic interactions [29,30,31]. Moreover, graphitization over DNPs can be enhanced by laser, dangling bonds, photon energy, metal ions and pHs [32,33,34,35,36]. These diamond/graphite (sp 3 /Sp 2 ) changes can be authenticated from Raman interrogations via in-plane bond stretching of sp 2 graphite sheath represented by G-band coexisted with locally disordered forbidden D-band [37].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, ultrathin graphite-diamond nanorods with 2.1 nm diameter were fabricated from diamond clusters through self-assembly using microwave plasma chemical vapor deposition (MPCVD) technique and then applied in field emission studies [41]. In contrast, our group recently reported a cost-effective wet chemical route for the construction of G-DNWs via pH induced self-assembly of cysteamine functionalized DNPs ( ND-Cys ) [36]. In a similar fashion, a metal ion mediated self-assembly of ND-Cys DNPs are delivered to provide the G-DNWs-like structure [42] which allow us to continue the perfection of such G-DNWs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation